Diazepam nasal spray administration is effective to control seizure clusters irrespective of time of day - Liow, Kore; Wheless, James W.; Cook, David F.; Rabinowicz, Adrian L.; Carrazana, Enrique (Frontiers in Neurology, 2024)
Introduction: Neurologic circadian influences, including sleep/wake transitions, processes (eg, hormonal variation), and behavioral patterns (eg, consumption of food and oral medications), may affect seizure patterns. Specific circadian patterns of seizures have been reported depending on type, onset location, and severity; however, data on patterns for patients with seizure clusters and effectiveness of rescue therapy by time of day are limited. Methods: We conducted post hoc analyses using patient diary data from the phase 3 safety study of diazepam nasal spray, which is indicated for acute treatment of seizure clusters in patients with epilepsy aged ≥6 years. Patients were administered age- and weight-based doses; second doses could be administered if needed to control a seizure cluster. We assessed clock timing of seizure-cluster onset along with second-dose use as a proxy for effectiveness. Treatment-emergent adverse events were recorded. Results: Seizure-cluster onset was observed to be generally highest during mornings and late evenings and lowest in the early evening and middle of the night. Second-dose use was not consistently associated with a specific time of day. The safety profile was consistent with that expected from previous studies of diazepam nasal spray. Conclusion: These results suggest that diazepam nasal spray can be effectively administered at any time of day.